Analisis Resepsi Khalayak pada Konten Keracunan Program Makan Bergizi Gratis (MBG) di Media Sosial TikTok - Nova Nurprianto; Made Dwi Adnjani (LANCAH: Jurnal Inovasi dan Tren, 2026)
This study was motivated by the proliferation of viral content on TikTok regarding food poisoning linked to the Free Nutritious Meal Program (MBG) from January to April 2026, which triggered a crisis of public trust. The objective of this study is to determine how the public interprets this content. This study employs Stuart Hall's reception theory, which categorizes audience positions into three groups: dominant, negotiating, and oppositional. The research approach is descriptive qualitative within a constructivist paradigm. Five informants were selected through purposive sampling, representing diverse backgrounds: MBG program recipients, teachers, nutrition students, student activists, and SPPG staff. The research subjects were three TikTok videos from the accounts @bbcnewsindonesia, @sctv_, and @papua.indonesia52. Data were collected through in-depth interviews and documentation, then analyzed using the Miles, Huberman, and Saldana model. The research findings indicate that all informants accepted the factual message that the food poisoning incident did indeed occur and that SPPG failed to maintain hygiene standards. All informants also agreed that SPPG's lack of transparency harmed the public and noted the irony between the program's name, "Nutritious Meals," and the reality of the food poisoning incident. However, attitudes toward the continuation of the Nutritious Meals program varied. Three informants (a student, a nutrition student, and an SPPG employee) supported the program with conditions, such as evaluation, sterilization, hygiene training, and stricter supervision. Meanwhile, the other two informants (a teacher and an activist) did not support the program. Four out of five informants were in a negotiating position, one was in a dominant position, and no one was in an opposing position. This study concludes that factual messages with strong visual evidence are difficult to reject; however, the informants' backgrounds such as direct experience, professional interests, scientific knowledge, ideology, and internal perspectives significantly influence the negotiation of meaning. The audience was found to be active in processing social media messages